A Federated Reference Structure for Open Informational Ecosystems. Issue 1 (17th May 2016) - Heinen, Richard; Kerres, Michael; Scharnberg, Gianna; Blees, Ingo; Rittberger, Marc
The paper describes the concept of a federated ecosystem for Open Educational Resources (OER) in the German education system. Here, a variety of OER repositories (ROER) (Muuß-Merholz & Schaumburg, 2014 ) and reference platforms have been established in the recent past. In order to develop this ecosystem, not only are metadata standards necessary, but also open Application Programming Interfaces (APIs) are required in order to exchange information. In conclusion, it is essential that all relevant stakeholders agree on an explicit policy to be developed collaboratively. A metadata exchange service can serve to connect all partners.